Accessibility, affordability, and equity in long-term spatial planning: Perspectives from a developing country. (May 2022) - van Heerden, Quintin; Karsten, Carike; Holloway, Jenny; Petzer, Engela; Burger, Paul; Mans, Gerbrand
Abstract: City planners attempt to create more equitable spaces by providing and improving access to benefits of living in cities, especially for previously disadvantaged urban communities. To this extent, evidence-based decision making is required to adequately plan for and improve accessibility to several types of facilities. Accessibility studies in literature focus mostly on one element, which is sufficient when presenting methodological advancements, but it is limiting when providing decision support to city planners. This paper argues that these measurements should be expanded and there is a need for a nuanced view on accessibility for improved urban planning practices. Such a view is presented by simultaneously considering various categories of supply (employment, housing, transportation, health, education, police), multiple modes of transport (walking, private vehicle, numerous transit modes), two cost thresholds (distance-based and monetary cost), level of access (percentage of facilities that can be reached), while distinguishing between the socio-economic profiles of regions in the city on the demand side. This improves the understanding of affordability and equity in the study of accessibility. Furthermore, this paper expands two categories (education and housing) to explain the influence of capacity on accessibility and equity. Lastly, it couples a land-use model to some of the accessibility measures to show the usefulness of using such a combination in long-term spatial planning and what the effects will be without government intervention, again contributing to the understanding of, and planning for, more inclusive and equitable cities. Highlights: Accessibility measures are presented in a nuanced manner. Supply, demand, modes, thresholds, and levels of access are combined. Socio-economic segmentation assists in understanding affordability and equity. Land-use models provide a futuristic view on accessibility measures. Segmented Lorenz curves and Gini coefficients inform accessibility inequality.